2018
DOI: 10.1380/ejssnt.2018.339
|View full text |Cite
|
Sign up to set email alerts
|

Applying Second and Third Resonance Frequencies to Surface Potential Measurements with Kelvin Probe Force Microscopy

Abstract: Frequency separation between topography and potential scans in Kelvin probe force microscopy (KPFM) was investigated. Topographic images were scanned via the first resonance frequency of the cantilever excited mechanically. Potential images were scanned via the first, second, or third resonance frequency of the cantilever excited electrostatically. Good separation of the mechanical modulation to the cantilever in AC mode and the potential modulation to the probe tip was obtained when the second or third modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…(5) We consider the capacitive terms to be equivalent for different eigenmodes, allowing for a direct division of the electrostatic force harmonics in order to access CPD. Some authors have indicated that the capacitance contribution of the lever differs at higher eigenmodes due to the mode shape of the cantilever [17,60,63]. This would primarily affect the accuracy of CPD for purely electrical modes dependent on C′ as the mechanically coupled modes dependent on C″ have minimal cantilever contribution [101].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(5) We consider the capacitive terms to be equivalent for different eigenmodes, allowing for a direct division of the electrostatic force harmonics in order to access CPD. Some authors have indicated that the capacitance contribution of the lever differs at higher eigenmodes due to the mode shape of the cantilever [17,60,63]. This would primarily affect the accuracy of CPD for purely electrical modes dependent on C′ as the mechanically coupled modes dependent on C″ have minimal cantilever contribution [101].…”
Section: Discussionmentioning
confidence: 99%
“…Higher eigenmodes typically have poorer SNRs than the fundamental eigenmode since k n increases more rapidly than Q n [60,61]. However, these modes still offer significant SNR enhancements over off-resonance techniques, higher spatial resolution due to reduced influence of the cantilever to the electrostatic forces [17,60,63], and higher bandwidth than side-band techniques [10,58]. All modes of KPFM can in principle be applied in any of these scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning Kelvin probe microscopy (SKPM) measures the contact potential difference between the sample and probe tip, corresponding to the work function. Recently, SKPM was used to characterize the work function of metallic samples and the surface potential of semiconductor samples . In this paper, the surface potential of NTO loaded with Au was measured by an SPM equipped with SKPM to determine the charge distribution under light illumination with different wavelengths and then to reveal the photocatalytic mechanism.…”
Section: Introductionmentioning
confidence: 99%